Femtosecond dynamics of BSCCO-2212 in the weak and strong excitation limits - Smith, D; Gay, P; Stevens, C; Chen, C; Yang, G; Abell, S; Wang, D; Wang, J; Ren, Z; Ryan, J (Elsevier, 2000)
We present measurements of the ultrafast optical response of BSCCO-2212 in the weak perturbation limit (photoexcitation density ≤10μJcm-2), where we focus attention on the dynamics of electronic correlations associated with the pseudogap, and also in the strong perturbation limit (≥1mJcm-2), where the superconducting condensate is destroyed.